Evaluación de variedades de papa de origen Holandés - Escalante, Wilfredo=700 1 Román Cortéz, Miguel; Bran, Jaime Vladimir
Sumario (Es)
Keywords: SOLANUM TUBEROSUM; VARIEDADES; CULTIVO; CARACTERISTICAS AGRONOMICAS; EL SALVADOR